Kikuchi's Disease: A Case Report (Faridpur Medical College Journal, 2014)
Kikuchi's disease is also known as histiocytic necrotizing lymphadenitis. Kikuchi-Fujimoto disease (KFD) or histiocytic necrotizing lymphadenitis, is a rare benign, self-limiting cervical lymphadenitis of unknown etiology. It predominantly affects young women and can closely mimic infective and immunological disorders. Recognition of this condition is crucial, specially because it can easily be mistaken for tuberculosis, lymphoma, or even adenocarcinoma. We report an 18 years old girl who presented with fever and cervical lymphadenopathy. She had multiple enlarged cervical lymphadenopathy. Examination of other systems was normal. Laboratory investigations were also normal. Fine needle aspiration cytology of the cervical node was not done. The patient took a course of oral antibiotics. Since the patient did not respond, lymph node biopsy was done and the histological features suggested the diagnosis of Kikuchi's disease. The Patient was treated symptomatically and complete remission occurred in few weeks. Although the incidence of Kikuchi-Fujimoto disease is rare, clinicians should be aware of this condition as early recognition of the disease will minimize potentially harmful and unnecessary evaluations and treatments. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20395 Faridpur Med. Coll. J. 2013;8(2): 96-98